Origin of basement membrane type IV collagen in xenografted human epithelial tumor cell lines. - Cleutjens, J. P. (1990)
The origin of basement membrane (BM), deposited in epithelial neoplasms, was studied in xenografts of human tumor cell lines in nude mice and rats. Cell lines were chosen that in vitro do (WISH, KB) or do not (5583-E; HT-29) produce BM components, more specifically, type IV collagen. Basement membrane deposition was studied by immunohistochemistry, using species cross-reactive polyclonal anti-human type IV collagen antiserum, mouse- and rat-specific polyclonal anti-mouse type IV collagen antiserum, human-specific monoclonal anti-type-IV collagen antibody, and by in situ hybridization, using a 32S-labeled species cross-reactive cDNA probe, specific for type IV collagen mRNA. In the xenografts, species-cross-reactive anti-type-IV collagen antiserum demonstrated the presence of irregular and discontinuous BM. In 5583-E and HT-29 xenografts, only murine type IV collagen epitopes were detected. In contrast, in WISH and in KB xenografts, the BM stained human as well as murine type IV collagen epitopes. By in situ hybridization, type IV collagen mRNA was detectable in stromal cells only in 5583-E and HT-29 xenografts, but in both epithelial and stromal cells in WISH and KB xenografts. These results indicate that in this model system epithelial tumor cells and stromal (mesenchymal) cells are involved in the production and deposition of a BM.